2018
DOI: 10.3892/etm.2018.5785
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of recombinant plasmid expressing fusion antigen Ag85B-Rv3425 in management of acute tuberculosis infection in mice

Abstract: Abstract. The emergence of drug-resistant tuberculosis (TB) and HIV-TB co-infection fuels an urgent need to develop novel therapeutic approaches, including therapeutic vaccines. Therapeutic vaccines have been proven to be a good strategy by inducing antigen specific immune responses against TB infection. In the present study, a recombinant plasmid based on lentiviral vector expressing fusion antigen Ag85B-Rv3425 (A3), and was constructed the immunogenicity and treatment effects in TB mice were assessed. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The CFU count and pathological examination showed that the vaccine could reduce the bacterial population in the lungs and spleen by inhibiting the growth and reproduction of Mtb in vivo . A3-len can reduce the severity of lung tissue lesions, increase the body weight of mice with active TB gradually, fight against the injury wrought by acute Mtb infection, and provide immune protection for mice ( 140 , 141 ). Based on the A3 platform, Su et al.…”
Section: Novel Vaccines Based On Pe/ppe Family Proteins Against Tbmentioning
confidence: 99%
“…The CFU count and pathological examination showed that the vaccine could reduce the bacterial population in the lungs and spleen by inhibiting the growth and reproduction of Mtb in vivo . A3-len can reduce the severity of lung tissue lesions, increase the body weight of mice with active TB gradually, fight against the injury wrought by acute Mtb infection, and provide immune protection for mice ( 140 , 141 ). Based on the A3 platform, Su et al.…”
Section: Novel Vaccines Based On Pe/ppe Family Proteins Against Tbmentioning
confidence: 99%